THE RELATIONSHIP BETWEEN LEARNING INTEREST AND LEARNING INDEPENDENCE TOWARD MATHEMATICS LEARNING OUTCOMES - Yayan Ananda Dwijuniar; Rostien Puput Anggoro (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Student learning outcomes are influenced by several factors, both internal and external factors. Interest in learning and learning independence are several factors that may be related to learning outcomes. This study aims to determine whether there is a positive and significant relationship between learning interest and learning independence with class X students' learning outcomes in the even semester of Vocational High School (SMK) Muhammadiyah in the academic year 2018/2019. This research aims to determine whether there is a positive and significant relationship between learning interest and learning independence with mathematics learning outcomes of class X students of SMK Muhammadiyah Mlati Even Semester of the 2018/2019 school year. This study's population was class X SMK Muhammadiyah Mlati 2018/2019 school year, consisting of 3 classes. Samples were taken in class X Pharmacy with random sampling techniques to the class. Data collection techniques are done using a questionnaire method to obtain data on learning interest and learning independence and documentation methods to obtain learning outcome data. Research instrument test: reliability test. Analysis prerequisite test: normality test, linearity test, and independence test. Data analysis uses product moment analysis and multiple linear regression analysis. The results showed no positive and significant relationship between learning interest and learning independence with the learning outcomes of class X Even Semester Students of SMK Muhammadiyah Mlati Academic Year 2018/2019. This is indicated by Fcount = -73.25 and Ftable = 3.80 Fcount <Ftable with R = 0.25966 . Large RC= 92.72%,RC = 7.27%, EC= 6.25%, and EC= 0.490%.